2020
DOI: 10.1111/1541-4337.12640
|View full text |Cite
|
Sign up to set email alerts
|

Tofu products: A review of their raw materials, processing conditions, and packaging

Abstract: Tofu is a traditional product made mainly from soybeans, which has become globally popular because of its inclusion in vegetarian, vegan, and hypocaloric diets. However, with both commercial production of tofu and scientific research, it remains a challenge to produce tofu with high quality, high nutrition, and excellent flavor. This is because tofu production involves multiple complicated steps, such as soybean selection, utilization of appropriate coagulants, and tofu packaging. To make high-quality tofu pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(64 citation statements)
references
References 176 publications
(288 reference statements)
0
58
0
6
Order By: Relevance
“…The prediction of cost and supply for SPs is much easier than that for milk protein products, which makes cost management easy and increases the profitability of products. Highquality SPs may be used as financial substitutes for casein, milk protein concentrate, skim milk powder, whole milk powder, and whey protein-derived peptide material [149,150].…”
Section: Economic Feasibility and Application Of Soybean-derived Bioactive Peptidesmentioning
confidence: 99%
“…The prediction of cost and supply for SPs is much easier than that for milk protein products, which makes cost management easy and increases the profitability of products. Highquality SPs may be used as financial substitutes for casein, milk protein concentrate, skim milk powder, whole milk powder, and whey protein-derived peptide material [149,150].…”
Section: Economic Feasibility and Application Of Soybean-derived Bioactive Peptidesmentioning
confidence: 99%
“…At a certain temperature, GDL slowly hydrolyzes the gluconic acid and releases protons, which is a suitably gradual process for forming a continuous soy protein network structure through hydrophobic and electrostatic interactions [70]. Excessive gel rate can result in gel with an uneven structure and low strength [71]. Kaoru et al [60] showed that the gelation process of GDL is similar to that of salt-based coagulants, and its gelation curve conforms to first-order reaction kinetics.…”
Section: Acid Coagulantmentioning
confidence: 99%
“…SDS-PAGE analysis of tofu gels treated with different temperatures was performed to investigate the influence of thermal treatment on the soy protein aggregation. The 7S (β-conglycinin) and 11S (glycinin) globulins are the two main storage proteins, accounting for more than 70% of the total soybean protein content (Zheng et al, 2020). In general, 7S is composed of three subunits: α, α 0 , and β, and 11S is consisted of an acidic (A) polypeptide and a basic (B) polypeptide linked by a disulfide bond (Wu et al, 2018).…”
Section: Sds-page and Intermolecular Forces Of The Firm Tofu Gelsmentioning
confidence: 99%
“…shelf life of RTE firm tofu (Zheng, Regenstein, Teng, & Li, 2020). The tofu-based product obtained can be capable of being stored at room temperature.…”
Section: Introductionmentioning
confidence: 99%